2021
DOI: 10.1016/j.sjbs.2021.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling and antioxidant potential of Daphne mucronata Royle and action against paracetamol-induced hepatotoxicity and nephrotoxicity in rabbits

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this study, the level of MDA in the lung tissue of BLM-receiving animals showed a marked increase, which was consistent with the findings of Yang et al [ 42 ]. In this context, Nazir et al [ 43 ] documented that Daphne mucronata Royle exhibit antioxidant properties in the paracetamol-induced hepatotoxicity by reducing lipid peroxidation, which was characterized by a decrease in the MDA level. Furthermore, Betulin is reported to be a direct scavenger of free oxygen radicals in high-fat diet-induced non-alcoholic fatty liver disease by mitigating oxidative stress [ 44 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the level of MDA in the lung tissue of BLM-receiving animals showed a marked increase, which was consistent with the findings of Yang et al [ 42 ]. In this context, Nazir et al [ 43 ] documented that Daphne mucronata Royle exhibit antioxidant properties in the paracetamol-induced hepatotoxicity by reducing lipid peroxidation, which was characterized by a decrease in the MDA level. Furthermore, Betulin is reported to be a direct scavenger of free oxygen radicals in high-fat diet-induced non-alcoholic fatty liver disease by mitigating oxidative stress [ 44 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when combined with opioid analgesics, PTL can treat more severe pain, like post-operative pain and palliative care for advanced cancer patients (Popiolek and Porebski 2022 ). Although it is commonly considered safe and tolerable, overdose or excessive use can have serious consequences, including hematotoxicity (Yousef et al 2010 ), gastric ulcers (Rainsford and Whitehouse 2006 ), hepatotoxicity (Cairns et al 2019 ), impaired reproductive function (Pereira et al 2020 ), and kidney injury (Nazir et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Practical variations happen in the cell membrane as a consequence of the peroxidation of lipid [ 10 ]. CCl 4 is a potent lipid-soluble hepatotoxin bound to lipid and protein, and is used to enhance the peroxidative process [ 11 ]. Its toxic effect is dependent on the excessive production of the trichloromethyl peroxyl radical (CCl 3 • ) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%